1996
DOI: 10.1111/j.1471-0528.1996.tb09713.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal hysterectomy for the large uterus

Abstract: Objective To assess the feasibility and safety of performing vaginal hysterectomy on enlarged uteri the equivalent of 14 to 20 weeks of gestation in size. Design A prospective observational study. Setting The Royal Free Hospital, London. Participants Fourteen consecutive women undergoing vaginal hysterectomy for uterine fibroids up to 20 weeks in size. Interventions Vaginal hysterectomy with or without bilateral salpingo‐oophorectomy or oophorectomy. Main outcome measures Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 33 publications
4
103
1
2
Order By: Relevance
“…A 5mm trocar along with another 10 mm trocar was inserted in the lower abdomen. The stage-IV LAVH 10 began with electrocoagulation and transection of the bilateral round ligaments, the fallopian tubes and ovarian ligaments. Bilateral uterine arteries were identified and the vesico-uterine peritoneum was opened to make the subsequent hysterectomy easier to perform.…”
Section: Methodsmentioning
confidence: 99%
“…A 5mm trocar along with another 10 mm trocar was inserted in the lower abdomen. The stage-IV LAVH 10 began with electrocoagulation and transection of the bilateral round ligaments, the fallopian tubes and ovarian ligaments. Bilateral uterine arteries were identified and the vesico-uterine peritoneum was opened to make the subsequent hysterectomy easier to perform.…”
Section: Methodsmentioning
confidence: 99%
“…If the uterine size did not allow easy exteriorization, bisecting, coring, morcellation, enucleation of myomas or combinations of these volume-reducing techniques were performed [21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…18 Mean operating time was 92.03 min which is comparable to Magos A et al and Kovac et al which showed 84.3 and 94 minutes respectively. 19,2 Mean blood loss was 87.04 ml in our study. Blood loss ranged from 30 ml-160 ml in different studies.…”
Section: Discussionmentioning
confidence: 86%